A quantification of the relationship between neuronal responses in the rat rostral ventromedial medulla and noxious stimulation-evoked withdrawal reflexes - Devonshire, Ian M.; Kwok, C.H.T.; Suvik, Assaw; Haywood, Adrian R.; Cooper, Andrew H.; Hathway, G.J. (Wiley, 2015)
The rostral ventromedial medulla (RVM) regulates a range of involuntary behaviours but is most often associated with nociception via the action of pronociceptive ON cells and antinociceptive OFF cells. The phasic responses of ON and OFF cells determine whether or not incoming noxious signals provoke a withdrawal reflex, and previous studies have suggested that reflex RVM activity patterns actively shape motor output. Here we challenged the model by using juvenile rats, which are known to exhibit markedly different reflex responses compared with adults. By recording single-cell activity in the RVM and the electromyography responses of hindlimb flexor muscles to noxious thermal stimulation we found that the juvenile reflex had a shorter onset latency, was larger in amplitude and exhibited a decreased rise time compared with the adult reflex. The responses of ON and OFF cells faithfully tracked the shorter onset latency of the reflex by also responding earlier and, thus, still preceded the reflex. However, neither the reflex amplitude nor the ongoing response profile was predicted by the firing rate of RVM cells in either age group. Instead we found a close correspondence between RVM activity and the reflex only during the initiation of the response. Furthermore, the short rise time of the juvenile reflex was reflected in higher rates of change of both ON and OFF cell firing. Our data suggest that the RVM is associated only with the initiation of reflexes and does not shape ongoing muscle activity, which is more likely to be subserved by downstream spinal processes.